Sinonim Bahasa Sikka Dialek Tana Ai di Desa Ojandetun Kecamatan Wulanggitang Kabupaten Flores Timur - Rotan, Petrus Masan (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the form and meaning of synonyms for the Sikka language in the Tana Ai dialect in Ojandetun Village, Wulanggitang District, East Flores Regency. Thus the problems studied are (1) what are the forms and (2) what are the meanings of synonyms in the Sikka language of the Tana Ai dialect in Ojandetun Village, Wulanggitang District, East Flores Regency? The purpose of this study is to find and describe the form and meaning of synonyms for the Sikka dialect of Tana Ai in Ojandetun Village, Wulanggitang District, East Flores Regency.This research uses a qualitative approach. the method used is the listening and proficient method. The basic and advanced techniques of these two methods are the SLC, SBLC, fishing rod, face-to-face technique, note-taking, and documentation. The theory used is the Semantic theory.The results of the research prove that (1) the synonym forms of the Sikka Language Tana Ai dialect in Ojandetun Village, Wulanggitang District, East Flores Regency are generally in the form of monomorphemes in the verbal, nominal (no phoneme changes) category, and in the adjective category. (2) The meaning of synonym for the Sikka language of the Tana Ai dialect in Ojandetun Village, Wulanggitang District, East Flores Regency is the meaning of denotation and connotation.